Front Cover: Ultraviolet radiation oxidative stress affects eye health (J. Biophotonics 7/2018). Issue 7 (8th July 2018) - Ivanov, Iliya V.; Mappes, Timo; Schaupp, Patrick; Lappe, Christian; Wahl, Siegfried
Abstract : The role of ultraviolet radiation in oxidative stress‐related ocular pathologies is less known than its role in skin cancer. Excessive exposure to ultraviolet radiation is associated with increased oxidative stress in eye tissues, which may promote the development of photokeratitis, cataract, and retinal damages. Children are especially vulnerable: large pupils, transparent ocular media. Efficient everyday protection of the eye should be considered from early age. (Image: with permission from Carl Zeiss Vision International GmbH, Aalen, Germany) Further details can be found in the article by Iliya V. Ivanov, Timo Mappes, Patrick Schaupp, et al. (e201700377 ). Abstract : The role of ultraviolet radiation in oxidative stress‐related ocular pathologies is less known than its role in skin cancer. Excessive exposure to ultraviolet radiation is associated with increased oxidative stress in eye tissues, which may promote the development of photokeratitis, cataract, and retinal damages. Children are especially vulnerable: large pupils, transparent ocular media. Efficient everyday protection of the eye should be considered from early age. (Image: with permission from Carl Zeiss Vision International GmbH, Aalen, Germany) Further details can be found in the article by Iliya V. Ivanov, Timo Mappes, Patrick Schaupp, et al. (e201700377 ).